Śrīmahāgaṇapativākyārthavidvatsabhā 2009 (Śrīśrījagadguru Śaṅkarācārya Mahāsaṃsthānam, 2010)
Proceedings of the Vakyartha Vidwat Sabha held at Sringeri in 2009; consisted of deliberations in shastras such as vedanta, mimamsa, nyaya and vyakarana